First evaluation of QuantiFERON-TB Gold Plus performance in contact screening. Issue 5 (7th July 2016) - Barcellini, Lucia; Borroni, Emanuele; Brown, James; Brunetti, Enrico; Campisi, Daniela; Castellotti, Paola F.; Codecasa, Luigi R.; Cugnata, Federica; Di Serio, Clelia; Ferrarese, Maurizio; Goletti, Delia; Lipman, Marc; et al.
Identifying latently infected individuals is crucial for the elimination of tuberculosis (TB). We evaluated for the first time the performance of a new type of interferon-γ release assay, QuantiFERON-TB Plus (QFT-Plus), which includes an additional antigen tube (TB2), stimulating both CD4 + and CD8 + T-cells in contacts of TB patients. Contacts were screened for latent TB infection by tuberculin skin test, QFT-Plus and QuantiFERON-TB Gold in Tube (QFT-GIT). In 119 TB contacts, the overall agreement between QFT-Plus and QFT-GIT was high, with a Cohen's κ of 0.8. Discordant results were found in 12 subjects with negative QFT-GIT and positive QFT-Plus results. In analyses of markers of TB exposure and test results, the average time spent with the index case was the strongest risk factor for positivity in each of these tests. The difference in interferon-γ production between the two antigen tubes (TB2−TB1) was used as an estimate of CD8 + stimulation provided by the TB2. TB2−TB1 values >0.6 IU·mL −1 were significantly associated with proximity to the index case and European origin. QFT-Plus has a stronger association with surrogate measures of TB exposure than QFT-GIT in adults screened for latent TB infection. Interferon-γ response in the new antigen tube used an indirect estimate of specific CD8 + response correlates with increased Mycobacterium tuberculosis exposure, suggesting a possible role in identifying individuals with recent infection. QuantiFERON-TB Plus improved the diagnostic accuracy for latent TB infection in the setting of contact screening http://ow.ly/2Az0300SDg3